Non-linear static analysis of RC frame buildings using ecuadorian, colombian and peruvian codes - Viera Arroba, Luisa Paulina (2020)
Ecuador is located in a high seismicity zone. If we consider that many Ecuadorian structures are vulnerable, it is evident that the seismic risk in Ecuador is high. If the structure’s vulnerability is reduced the seismic risk will decrease, in this context the Building Construction Codes regulate the minimum requirements to obtain safe structures for their users, however, there are not many studies comparing the vulnerability obtained using Ecuadorian Construction Code (NEC-15) regarding the vulnerability obtained using other Constructions Codes. To understand the degree of vulnerability of reinforced concrete structures designed with NEC-15 has regarding those designed using National Construction Codes of Ecuador’s nearby countries, will allow us to recommend improvements to NEC-15. To do that, we designed 18 reinforced concrete building using NEC-15 and Colombia and Peru Construction Codes (NSR10 and E030, respectively). Considering the recommendations of these 3 National Constructions Codes, we obtain parameters required to carry out a nonlinear static analysis and from this data, we assessed the vulnerability of these buildings using the capacity spectrum method. We concluded that the application of the NSR-10 reflects a lower degree of vulnerability in the structures, even though buildings designed using E.030 were more rigid, also we found that structures designed under the same conditions with NEC-15 are more vulnerable than structures designed using NSR and E030. Still that, this vulnerability may change if other structural configurations are used, which we suggested as future work.